Achieve ultrahigh energy storage performance in BaTiO3–Bi(Mg1/2Ti1/2)O3 relaxor ferroelectric ceramics via nano-scale polarization mismatch and reconstruction. (January 2020) - Hu, Qingyuan; Tian, Ye; Zhu, Qingshan; Bian, Jihong; Jin, Li; Du, Hongliang; Alikin, D.O.; Shur, V. Ya; Feng, Yujun; Xu, Zhuo; Wei, Xiaoyong
Abstract: Development of lead-free dielectric ceramics with large recoverable energy storage density ( W rec ), high energy storage efficiency ( η ) and wide usage temperature range is of great significance to improve the overall performance of power electronic devices. Despite the numerous research efforts, performance of existing lead-free dielectric ceramics is barely satisfactory. Herein, an effective strategy to achieve ultrahigh energy storage performance via nano-scale polarization mismatch and reconstruction is proposed. By developing solid solutions of A-site coupling and B-site coupling ferroelectrics, polarization mismatch and ultrahigh energy storage performance can be realized in intermediated compositions. It is demonstrated that ultrahigh energy storage performance with a η of 93% and a W rec of 4.49 J/cm 3 is achieved in the 0.6BaTiO3 -0.4Bi(Mg1/2 Ti1/2 )O3 (0.6BT-0.4BMT) ceramic, which is a record high energy storage property in lead-free relaxor ferroelectric bulk ceramics. Excellent temperature stability with a variation of W rec and η less than 5% is also realized in a wide temperature range from 30 °C to 170 °C. Such an ultrahigh energy storage performance not only verifies our strategy, but also makes the 0.6BT-0.4BMT ceramic a promising candidate material for energy storage. Moreover, of particular significance is that this work provides an effective method to design novel high performance dielectric ceramics for future energy storage devices. Graphical abstract: Image 1 Highlights: A Wrec of 4.49 J/cm 3 and η of 93% are achieved in the 0.6BT-0.4BMT ceramic, which is record high in lead-free relaxor ferroelectric bulk ceramics. Excellent thermal stability with a variation less than 5% (from 30 °C to 170 °C) of the energy storage property is also achieved. Such an ultrahigh energy storage property verifies the effectiveness of our nano-scale polarization mismatch strategy.